Internal migration and agricultural labor mobility issues and policies in Ethiopia - Dessalegn, Mengistu (University of London, 2023)
Ethiopia’s economy is dominated by agriculture, contributing 45% to 50% of gross domestic product (GDP) and employing 70% of the active workforce. Most farming remains characterized by smallholder plots, with rainfed systems predominating, yet increasingly vulnerable because of uncertain rainfall and temperature patterns. In addition, due to a complex of factors, farmland frequently suffers from the depletion of soil nutrients. As a result of too few new jobs and the rapidly expanding economically active population, about two million more people are added annually to the labor market. As a result, there is considerable international migration to the Gulf States, South Africa, Europe and North America. Internal rural-to-urban migration is also common, mainly to major cities and towns, especially to Addis Ababa and other major centers in south and southwest Ethiopia.